Associations between child mobile use and digital parenting style in Hungarian families. Issue 1 (2nd January 2020) - Konok, Veronika; Bunford, Nóra; Miklósi, Ádám
ABSTRACT: Mobile touch screen device (MTSDs) use is becoming widespread in children and has negative and positive consequences. Yet, factors associated with greater use remain unexplored, despite the importance of their identification for intervention purposes. It stands to reason that parents can influence child MTSD use, via their attitudes, beliefs, role-modelling, and style of parenting. Here, we examined the associations between these parental characteristics and child MTSD use and whether parenting styles specifically with regard to child MTSD use exist. Hungarian parents ( N = 1283) were surveyed about their children's digital activities, their own attitudes and beliefs regarding the child's MTSD use, and their own attachment to- and use of mobile phones. Taking a data-driven approach, distinct "digital parenting styles" were identified and these resembled general parenting styles. Findings further suggested that children spent more time with MTSD use if their parents: were more permissive, more authoritative and less authoritarian; had a lower educational level; exhibited greater attachment to their mobile phones; and had more positive attitudes towards, and attributed less harm and more benefits to, early device use. These results are the first evidence for existence of digital parenting styles and suggest that parental characteristics are potential prevention and treatment targets.